Nursing in the Care of Neurosurgical Patients using External Ventricular Drain: experience report (Research, Society and Development, 2021)
Objective: to describe the nursing care provided to hemorrhagic stroke patients using an external ventricular drain. Method: a descriptive study, of experience report type, carried out in June 2021. The study site is in a public university hospital in Southern Brazil. Results: on admission, the nurse is responsible for making sure of the location and permeability of the ventricular drainage, positioning the patient in dorsal decubitus, with sternal alignment and head of the bed at 30º. To install the system, it is necessary to couple the transducer to the multi-parameter monitor, and the zero point of the system must be aligned with the external acoustic meatus, using a leveling ruler. The system is then fixed on a support exclusively for this purpose, maintaining the point height for the cerebrospinal fluid drainage at 20 centimeters above the transducer or the zero point, considering a normal intracranial pressure of up to 15 mmHg. When necessary to change the bed headboard height, the proximal circuit of the patient's head should be interrupted, closing the clamp, keeping the drainage bag well fixed, avoiding level changes and inadvertent drainage. Final considerations: the complexity of care for neuro-critical patients is evident, thus highlighting the need for the implementation of interventions based on specific care plans to obtain the appropriate treatment.